Decreasing Family Anxiety Level of Acute Coroner Syndrome with Slow Deep Breathing Relaxation - Zulkifli B Pomalango; Titin A Wihastuti; Yulian W Utami (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2020)
Acute Coronary Syndrome Patients can cause anxiety for the family. Anxiety of ACS family in Aloei Saboe hospital was found to be a family of moderate anxiety of 18 people (81.8%) and a severe anxiety of 4 people (18.2%). This study used the research design of One Group Pretest Posttest Design with 22 respondents. Respondents were given slow deep breathing exercises, given for 15 minutes. The bivariate analysis used is the Marginal Homogeneity Test. The results of the study were obtained before being given treatment, the family with moderate anxiety amounted to 18 people (81.8%) and a heavy anxiety of 4 people (18.2). After being given treatment there was a decrease in the level of anxiety, the family with moderate anxiety numbered 9 people (40.9) and mild anxiety about 13 people (59.1%). The results of the statistical test for marginal homogeneity obtained p values of 0.000 (p<0.05). There is a slow deep breathing effect on decreasing family anxiety level of acute coronary syndrome patients. Further research, slow deep breathing actions can be combined with health education in overcoming the anxiety of families who care for patients in hospitals.